Eye structure shapes neuron function in Drosophila motion vision - Arthur Zhao; Eyal Gruntman; Aljoscha Nern; Nirmala Iyer; Edward M. Rogers; Sanna Koskela; Igor Siwanowicz; Marisa Dreher; Miriam A. Flynn; Connor Laughland; Henrique Ludwig; Alexander Thomson; et al. (Nature, 2025)
Abstract Many animals use vision to navigate their environment. The pattern of changes that self-motion induces in the visual scene, referred to as optic flow1, is first estimated in local patches by directionally selective neurons2–4. However, how arrays of directionally selective neurons, each responsive to motion in a preferred direction at specific retinal positions, are organized to support robust decoding of optic flow by downstream circuits is unclear. Understanding this global organization requires mapping fine, local features of neurons across an animal’s field of view3. In Drosophila, the asymmetrical dendrites of the T4 and T5 directionally selective neurons establish their preferred direction, which makes it possible to predict directional tuning from anatomy4,5. Here we show that the organization of the compound eye shapes the systematic variation in the preferred directions of directionally selective neurons across the entire visual field. To estimate the preferred directions across the visual field, we reconstructed hundreds of T4 neurons in an electron-microscopy volume of the full adult fly brain6, and discovered unexpectedly stereotypical dendritic arborizations. We then used whole-head micro-computed-tomography scans to map the viewing directions of all compound eye facets, and found a non-uniform sampling of visual space that explains the spatial variation in preferred directions. Our findings show that the global organization of the directionally selective neurons’ preferred directions is determined mainly by the fly’s compound eye, revealing the intimate connections between eye structure, functional properties of neurons and locomotion control.